2017
DOI: 10.1161/circulationaha.116.023255
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of N-Terminal Pro-B-Type Natriuretic Peptide, Troponin-T, and Growth-Differentiation Factor 15 in Adult Congenital Heart Disease

Abstract: NT-proBNP provides prognostic information beyond a conventional risk marker model in patients with ACHD and can reliably exclude the risk of death and heart failure. Elevated levels of NT-proBNP, high-sensitive troponin-T, and growth-differentiation factor 15 identify patients at highest risk of cardiovascular events. These biomarkers therefore may play an important role in the monitoring and management of patients with ACHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 49 publications
5
101
1
Order By: Relevance
“…After complete adjustment for all covariates, the strength of the association was slightly attenuated but remained significant for both the primary end point (adjusted HR per 2‐fold higher value 1.39 [95% CI 1.23–1.57], P <0.001) and the secondary end point (adjusted HR per 2‐fold higher value 1.80 [95% CI 1.42–2.28], P <0.001). The prognostic value of baseline NT‐proBNP in this cohort has been previously published (using standardized HRs) . Of note, baseline eGFR measurements were not predictive of the primary and secondary end point in these multivariable models (adjusted HR per 2‐fold higher value 1.00 [95% CI 0.58–1.72], P =0.993 and 2.49 [95% CI 0.78–7.89], P =0.123, respectively).…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…After complete adjustment for all covariates, the strength of the association was slightly attenuated but remained significant for both the primary end point (adjusted HR per 2‐fold higher value 1.39 [95% CI 1.23–1.57], P <0.001) and the secondary end point (adjusted HR per 2‐fold higher value 1.80 [95% CI 1.42–2.28], P <0.001). The prognostic value of baseline NT‐proBNP in this cohort has been previously published (using standardized HRs) . Of note, baseline eGFR measurements were not predictive of the primary and secondary end point in these multivariable models (adjusted HR per 2‐fold higher value 1.00 [95% CI 0.58–1.72], P =0.993 and 2.49 [95% CI 0.78–7.89], P =0.123, respectively).…”
Section: Resultsmentioning
confidence: 56%
“…Right ventricular systolic pressure was available in 420 patients (71%), of whom 33 patients (7.9%) had pulmonary hypertension. A flowchart of the patient selection and detailed clinical, electrocardiographic and echocardiographic characteristics of the study cohort, also expressed per baseline NT‐proBNP quartile, have been previously reported …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Framingham Heart Study, patients followed for 11 years who had elevated GDF-15 (median concentration 1066 ng/L ± 594) were found to have increased risk for incident heart failure (HR 1.52, 95% CI 1.29–1.78) [44]. While predictive for incident heart failure in isolation, the added value of GDF-15 to BNP or NT-proBNP is relatively modest [42]. …”
Section: Novel Markers Of Inflammation Fibrosis and Contractilitymentioning
confidence: 99%
“…Second controversy associated with clinical evidence of advantages of individually adjusted multiple marker approaches in provision of the greatest prognostic improvement among patients with various HF phenotypes [22,23]. Although GDF-15 was useful to detect prevalent of any HF phenotype in addition to NPs, the discriminative value of NPs, GDF-15, sST2, galectin-3 and cardiac troponins in general population was similar [24,25]. Third controversy is follow: In obese and diabetes mellitus subjects GDF-15 was the best predictor for all-cause mortality to NPs, while discriminative value for both markers in combination was not better than single biomarker use [26].…”
Section: Introductionmentioning
confidence: 99%